Western lifestyle as a driver of dysbiosis in colorectal cancer - Nora J. Foegeding; Zachary S. Jones; Mariana X. Byndloss (The Company of Biologists, 2021)
Landmark discoveries in the gut microbiome field have paved the way for new research aimed at illuminating the influence of microbiota in colorectal cancer. A major challenge is to account for the effect of inherently variable environmental factors on the host and the gut microbiome, while concurrently determining their contribution to carcinogenesis. Here, we briefly discuss the role of the gut microbial community in colorectal cancer and elaborate on the recent insight that environmental factors related to a Western diet and lifestyle may drive the bloom of tumorigenic members of the gut microbiota. We also discuss how future research focused on untangling host-microbe interactions in the colon may influence medical insights that relate to the prevention and treatment of colorectal cancer.